1997
DOI: 10.1136/bmj.315.7102.216
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cleansing the birth canal with antiseptic solution on maternal and newborn morbidity and mortality in malawi: clinical trial

Abstract: Objective: To estimate the contribution of excessive alcohol use to socioeconomic variation in mortality among men and women in Finland. Design: Register based follow up study. Subjects: The population covered by the 1985 and 1990 censuses, aged >20 in the follow up period 1987-93. Main outcome measures: Total mortality and alcohol related mortality from all causes, from diseases, and from accidents and violence according to socioeconomic position. The excess mortality among other classes compared with upper n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
66
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(70 citation statements)
references
References 10 publications
1
66
0
3
Order By: Relevance
“…A study of the impact of chlorhexidine cleansing was undertaken in Malawi at an urban hospital, at a cost of $0.10 for each maternal-infant pair treated (Table 25). 427,428 Cleansing of the maternal vaginal canal and the newborn skin with a 0.25% chlorhexidine solution resulted in significant reductions in serious postpartum maternal infections (P ϭ .02), neonatal admissions (OR: 0.8; CI: 0.79 -0.97), neonatal sepsis (OR: 0.5; CI: 0.32-0.76), overall neonatal mortality (28.6 vs 36.9 per 1000; P Ͻ .05), and neonatal mortality due to infections (OR: 0.5; CI: 0.29 -0.88; 2.4 vs 7.3 per 1000; P Ͻ .005). 428 Among women with rupture of membranes for Ͼ4 hours, the HIV transmission rate was decreased by 40% (OR: 0.6; CI: 0.4 -0.9).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…A study of the impact of chlorhexidine cleansing was undertaken in Malawi at an urban hospital, at a cost of $0.10 for each maternal-infant pair treated (Table 25). 427,428 Cleansing of the maternal vaginal canal and the newborn skin with a 0.25% chlorhexidine solution resulted in significant reductions in serious postpartum maternal infections (P ϭ .02), neonatal admissions (OR: 0.8; CI: 0.79 -0.97), neonatal sepsis (OR: 0.5; CI: 0.32-0.76), overall neonatal mortality (28.6 vs 36.9 per 1000; P Ͻ .05), and neonatal mortality due to infections (OR: 0.5; CI: 0.29 -0.88; 2.4 vs 7.3 per 1000; P Ͻ .005). 428 Among women with rupture of membranes for Ͼ4 hours, the HIV transmission rate was decreased by 40% (OR: 0.6; CI: 0.4 -0.9).…”
Section: )mentioning
confidence: 99%
“…427,428 Cleansing of the maternal vaginal canal and the newborn skin with a 0.25% chlorhexidine solution resulted in significant reductions in serious postpartum maternal infections (P ϭ .02), neonatal admissions (OR: 0.8; CI: 0.79 -0.97), neonatal sepsis (OR: 0.5; CI: 0.32-0.76), overall neonatal mortality (28.6 vs 36.9 per 1000; P Ͻ .05), and neonatal mortality due to infections (OR: 0.5; CI: 0.29 -0.88; 2.4 vs 7.3 per 1000; P Ͻ .005). 428 Among women with rupture of membranes for Ͼ4 hours, the HIV transmission rate was decreased by 40% (OR: 0.6; CI: 0.4 -0.9). In another study in Kenya comparing intrapartum vaginal lavage with 0.2% and 0.4% chlorhexidine, there was no overall effect on transmission of HIV, but risk of transmission was significantly reduced (OR: 0.1; CI: 0.0 -0.9) in the subgroup that had not had rupture of membranes before treatment.…”
Section: )mentioning
confidence: 99%
“…5 Intral l partum use of chlorhexidine, coupled with communitylbased interventions to improve hygiene (such as handlwashing and clean delivery) and neonatal care practices (clean cord cutting and care, skin care) may reduce the incidence of neonatal infections. 6,38,44,45 Later deaths from infections including tetanus can be strongly linked to environmental exposures and practices during home delivery and care. 6 Neonatal tetanus can be prevented through maternal tetanus immunization, as well as clean cord care.…”
Section: 6mentioning
confidence: 99%
“…33 Recent evidence suggests that iml l proved care of preterm or LBW infants can substantially improve survival. 5,6 Early postnatal vitamin A dosing; 34 promotion of early and exclusive breastl l feeding; 6,35 hypothermia prevention and management, including skinltolskin care; 36,37 topical skin cleansing with chlorhexidine; 38,39 and topical emollient treatment for hospitalized infants 40,41 may also reduce mortality and morbidity in LBW or preterm neonates. 5,42,43 Furl l thermore, the substantial proportion of early deaths that occurred in the absence of distinct symptoms suggests that prol l grammes to reduce neonatal mortality should also focus on routine, preventive care for all newborn babies in addition to responding to carelseeking for perceived presence of danger signs.…”
Section: 6mentioning
confidence: 99%
“…Following this landmark study, different ART regimens have demonstrated variable impact in the reduction of HIV-1 vertical transmission rates (Dabis et al 1999, Guay et al 1999, Shaffer et al 1999, Wiktor et al 1999, PST 2002, Lallemant et al 2004, Read et al 2007). In addition to ART, other interventions have contributed to the reduction of HIV-1 vertical transmission, such as elective cesarean section (C-section) (IPHIVG 1999, EMDC 1999, vaginal cleaning during the intrapartum period (Taha et al 1997), vitamin A supplementation (Semba 1997), and avoidance of breastfeeding (Nduati et al 2001, RoUsseau et al 2004.…”
mentioning
confidence: 99%